Bionic superhydrophobic surfaces based on topography of copper oxides. Issue 3 (17th August 2022) - Chen, Chen; Zhan, Haiyang; Bai, Xiangge; Yuan, Zichao; Zhao, Lei; Liu, Yahua; Feng, Shile
Abstract: Superhydrophobic surfaces (SHSs) exist in many biological organisms endowed by spectacular surface topographies, which provide important insights to drive a paradigm shift in design of engineering surfaces. Based on this, extensive progresses have been developed on bionic superhydrophobic strategies. Among them, SHSs based on topography of copper oxides exhibit considerable application prospects because of the steerability and diversity of topography, as well as additional performances, such as antibiosis, anticorrosion and catalysis. We first present a brief overview of the discovery of natural SHSs as well as fundamental understanding of surface wetting performance. Then, the structural effects in superhydrophobic systems based on the topographies of biological organisms and copper oxides are described. Finally, we highlight the perspectives on the novel design strategies of copper oxide‐based SHSs that adapt to various practical applications.